Estimation of Total Water Demand in the Command Area of Bapatla Channel - Sahithya, K.; Babu, G. Ravi; Mani, A.; Rao, Ch. Sujani (International Journal of Economic Plants, 2021)
Estimating irrigation water requirements is prerequisite for water project planning and management. A study was carried out to determine the crop water requirement of selected crops for the command area of Bapatla channel. The major crops include paddy and maize for two seasons (kharif and rabi). CROPWAT 8.0 was used to estimate the reference evapotranspiration, crop water requirement and irrigation water requirement. The information about climatic conditions, soil types and cropping pattern were obtained for the period of 2012-13 to 2016-17 (5 years) and used as input data for CROPWAT. Average peak monthly reference evapotranspiration (ETo) was observed to be 6.65 mm day-1 for the month of May. Whereas average minimum ETo was observed as 3.28 mm day-1 in the month of December. The results obtained as the TWD (Total Water Demand) of Bapatla channel command for two seasons (kharif and rabi) of crops paddy and maize was found to be 6500.04 ha-m in the year 2012-13. Similarly, for 2013-14, 2014-15, 2015-16 and 2016-17 years TWD was found to be 6325.18, 6521.42, 3102.40 and 5376.19 ha-m, respectively. It was observed that total water demand (TWD) was least in the year 2015-16 (3102.40 ha-m) and maximum in the year 2014-15 (6521.42 ha-m).